NATURAL CONSTRAINTS ON METAMORPHIC REACTION RATES - Baxter E.F. (My University, 2003)
Quantitative constraints on the rates at which metamorphic reactions proceed in nature are now available from several sources. Most common are predictions made on the basis of laboratory kinetic data. However, the applicability of such laboratory-based predictions has long been questioned and many observations in the field now suggest much slower rates. Here, published quantitative field-based constraints on high temperature (> 400 degrees C) reaction rates are assembled from a variety of sources. Reaction rates attending regional metamorphism are four to seven orders of magnitude slower than most laboratory-based predictions. A general rate law for regional metamorphism has been derived which best describes these field-based data: log(10) (R(net)) congruent to 0.0029T - 9.6 +/- 1 where R(net) is the net reaction rate (g/cm(2)/a) and T is temperature (degrees C). At the same time, natural reaction rates attending contact metamorphism differ from laboratory-based predictions by less than two orders of magnitude, and are in close agreement at higher temperatures. Thus, while existing laboratory-based kinetic data may be judiciously applied to some contact metamorphic systems, laboratory-based kinetic predictions clearly misrepresent regional metamorphism. To explain this kinetic discrepancy, regional metamorphic reaction rates may be limited by slow intergranular transport due to comparatively limited (or transient) availability of aqueous fluid in the intergranular medium. The general field-based rate law may be applied to regional metamorphic, and other environments (i.e. ultrahigh pressure or ultrahigh temperature metamorphism), if similar system characteristics (mainly, low aqueous fluid content) can be inferred.